Rumination in children from broken home: Can self-compassion and emotional intelligence reduce rumination? - Amalia Juniarly; Sayang Ajeng Mardhiyah; Nissah Ghina Fitri (Jurnal Psikologi Terapan dan Pendidikan, 2021)
Although research on rumination and self-compassion has been done before, none of them examined rumination, self-compassion, and emotional intelligence simultaneously. This study aims to determine the role of self-compassion and emotional intelligence on rumination. The study participants were 200 adolescents aged 10-21 years and whose parents are divorced. Researchers used rumination, self-compassion and emotional intelligence measuring instrument and distributed the instrument through google form in the data collection process. Multiple regression analysis results indicate that self-compassion and emotional intelligence have a significant role in reducing rumination. Researchers found that adolescents mostly used mindfulness (M=18.00; SD=3.544), reflection (M=25.59; SD=5.364), and aspects of self-motivation (M=17.86; SD=2.313) to regulate emotions, and feel the benefits of components in everyday life.